Invoking posthumanist vistas: A diffractive gaze on curriculum practices and potential - Maistry , S.; Sabelis, I.; Simmonds, S. (South African Journal of Higher Education, 2023)
Humanist discourse has assumed such an ideological normalcy to the extent that any attempts at its disruption are likely to be met with severe resistance. As such, higher education curriculum design and curriculum content continue to be largely anthropocentric, buoyed by human-centred neoliberal principles that have gradually encroached the academe. To explore ways out of the dilemma, we draw on wild pedagogy theory (Jickling 2015; Mcphie and Clarke 2015; Springgay and Zaliwska 2017; Jickling et al. 2018b) as a means to challenge the straitjacket constraints of neoliberal higher education. Over time, the wild has been banished from classrooms: the call for wild pedagogies might mean that we have reached the limits of the “tamed” ‒ and we have tamed a lot in order to offer a “one size fits all” approach to (higher) education (Jickling et al. 2018a). The tendency for higher education to teach more and more people in less and less time, has implied an understanding of teaching that is characterised by efficiency and processing, at the cost of the process of learning as a relational becoming with the world in the posthuman condition we live in (Braidotti 2019). In this article, vignettes are used to offer an account of our critical posthumanist incursions as university lecturers into curriculum practices. We use a diffractive gaze to present the generative potential of non-anthropocentric approaches as well as the struggles that these present as we strive to de-center our humanistic tendencies towards curriculum knowledge and teaching within the neoliberal space, we find ourselves.